Interaction of tarantula venom peptide ProTx-II with lipid membranes is a prerequisite for its inhibition of human voltage-gated sodium channel NaV 1.7 - Henriques, S.; Deplazes, Evelyne; Lawrence, N.; Cheneval, O.; Chaousis, S.; Inserra, M.; Thongyoo, P.; King, G.; Mark, A.; Vetter, I.; Craik, D.; Schroeder, C. (The American Society for Biochemistry and Molecular Biology Inc, 2016)
ProTx-II is a disulfide-rich peptide toxin from tarantula venom able to inhibit the human voltage-gated sodium channel 1.7 (hNaV 1.7), a channel reported to be involved in nociception, and thus it might have potential as a pain therapeutic. ProTx-II acts by binding to the membrane-embedded voltage sensor domain of hNaV 1.7, but the precise peptide channel-binding site and the importance of membrane binding on the inhibitory activity of ProTx-II remain unknown. In this study, we examined the structure and membrane-binding properties of ProTx-II and several analogues using NMR spectroscopy, surface plasmon resonance, fluorescence spectroscopy, and molecular dynamics simulations. Our results show a direct correlation between ProTx-II membrane binding affinity and its potency as an hNaV 1.7 channel inhibitor. The data support a model whereby a hydrophobic patch on the ProTx-II surface anchors the molecule at the cell surface in a position that optimizes interaction of the peptide with the binding site on the voltage sensor domain. This is the first study to demonstrate that binding of ProTx-II to the lipid membrane is directly linked to its potency as an hNaV 1.7 channel inhibitor.